Microdiscectomy Results using the Caspar Technique. Issue 1 (April 2016) - Velnar, Tomaz; Bunc, Gorazd
Introduction: The degenerative disease of the intervertebral disc and back pain are chronic conditions and represent an important cause of morbidity and mortality. Treatment of lumbar radicular compressive syndromes is described, as well as the success of microsurgical procedure according to the Caspar technique. Material and Methods: In the prospective study, 100 patients were included. All suffered from the radiculopathy due to the nerve compression. Conservative treatment was not successful and operation was then performed. The follow up of patients was evaluated from 1 to 3 years after the operation, the average time was 17 months. Results: The results showed excellent outcome in 67%, good outcome in 28%, fair in 1% and poor in 3% of patients. One patient died one month after the operation due to unrelated reasons and was not included in the final assessment. Thus, the total result was satisfactory in 95%. Conclusion: The results of microsurgical approach showed that the efficiency of such operation in this series can be compared with similar results elsewhere according to the international criteria (88% to 98%). The successfulness of the microsurgical method is due to gentle tissue handling, especially with respect to the nerve structures in the spinal canal and considerably smaller injury if muscles and bone. This is achieved by better visibility and field magnification with the operative microscope.